Implementation of a Marketing Mix Strategy in an Effort to Increase Sales of Coffee Products in Blitar Seberang Village, Sindang Kelingi District, Rejang Lebong Regency Buka di Google Terjema - Sri Handayani; Andriyani Prawitasari; Dennis Ryanto Tambu; Kresnawati Kresnawati; Asty Eka Fitriani (Universitas Dehasen Bengkulu, 2023)
The success of the marketing strategy is influenced by several factors, namely market research and analysis, decisions about products, pricing, promotion and distribution (marketing mix). The purpose of this community service is to provide an understanding of the marketing mix (marketing mix) in an effort to increase sales of coffee products and able to apply the marketing mix process to businesses that are run based on the needs and desires of consumers. This community service activity (PKM) is in collaboration with the people of Blitar Seberang Village, Merigi Kelindang District, Rejang Lebong Regency, who chose the coffee business to become partners. Lack of understanding in pricing, how to market products, and provide promos needs to be prepared. With these problems, the solutions offered are conducting outreach and training in pricing how to market products, and providing promos. The method in this PkM activity begins with the preparation stage, the implementation stage and the reporting stage which are planned within 1 month to complete. The results and outcomes of this PkM activity are that partners have understood pricing on how to market products and provide promos, as well as training on pricing on how to market products and provide promos can operate and be utilized in their marketing activities